Risk factors for acute ischemic stroke caused by anterior large vessel occlusion - Hendrix, Philipp (Stroke, 2019)
BACKGROUND AND PURPOSE: Accurate prediction of acute ischemic stroke (AIS) caused by anterior large vessel occlusion (LVO) that is amendable to mechanical thrombectomy remains a challenge. We developed and validated a prediction model for anterior circulation LVO stroke using past medical history elements present on admission and neurologic examination. METHODS: We retrospectively reviewed AIS patients admitted between 2009 and 2017 to three hospitals within a large healthcare system in the United States. Patients with occlusions of the internal carotid artery or M1 or M2 segments of the middle cerebral artery were randomly split into 2/3 derivation and 1/3 validation cohorts for development of an anterior circulation LVO prediction model and score that was further curtailed for potential use in the prehospital setting. RESULTS: A total of 1,654 AIS were reviewed, including 248 (15%) with anterior circulation LVO AIS. In the derivation cohort, National Institute of Health Stroke Score Scale (NIHSS) at the time of cerebrovascular imaging, current smoking status, type 2 diabetes mellitus, extracranial carotid, and intracranial atherosclerotic stenosis were significantly associated with anterior circulation LVO stroke. The prehospital score was curtailed to NIHSS, current smoking status, and type 2 diabetes mellitus. The area under the curve for the prediction model, prehospital score, and NIHSS alone were 0.796, 0.757, and 0.725 for the derivation cohort, and 0.770, 0.689, and 0.665 for the validation cohort, respectively. The Youden index J was 0.46 for a score of > 6 with 84.7% sensitivity and 62.0% specificity. CONCLUSIONS: Previously reported LVO stroke prediction scores focus solely on elements of the neurologic exam. In addition to stroke severity, smoking, diabetes mellitus, extracranial carotid, and intracranial atherosclerotic stenosis were associated with anterior circulation LVO AIS. While atherosclerotic stenosis may not be known until imaging is obtained, smoking and diabetes mellitus history can be readily obtained in the field and represent important elements of the prehospital score supplementing NIHSS.